2015
DOI: 10.1007/s10903-015-0327-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Chronic Disease and Their Risk Factors Among Iranian, Ukrainian, Vietnamese Refugees in California, 2002–2011

Abstract: Little is known about how the health status of incoming refugees to the United States compares to that of the general population. We used logistic regression to assess whether country of origin is associated with prevalence of hypertension, obesity, type-II diabetes, and tobacco-use among Iranian, Ukrainian and Vietnamese refugees arriving in California from 2002 to 2011 (N = 21,968). We then compared the prevalence among refugees to that of the Californian general population (CGP). Ukrainian origin was positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 23 publications
0
29
0
Order By: Relevance
“… Authors (Year) D.M. Hyperlipidemia Hypertension Obesity Psychosocial Tobacco Bo et al (2015) [ 25 ] NR NR NR NR NR NR Linton et al (2020) [ 34 ] NR NR NR NR NR NR Nguyen et al (2016) [ 22 ] Iran (↓) NR Iran (↓) Iran (↑) NR Iran (↑) Ukraine (↓) Vietnam (↑) Ukraine (↓) Ukraine (↓) Ukraine (↑) Vietnam (↓) Vietnam (↓) Vietnam (↓) Njeru et al (2016) [ 23 ] NS NR NR Norredam et al (2014) [ 20 ] NR NR NR NR NR van Oostrum et al (2011) [ 24 ] NR NR NR NR NR Yun et al (2012) [ 21 ] NS NR …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… Authors (Year) D.M. Hyperlipidemia Hypertension Obesity Psychosocial Tobacco Bo et al (2015) [ 25 ] NR NR NR NR NR NR Linton et al (2020) [ 34 ] NR NR NR NR NR NR Nguyen et al (2016) [ 22 ] Iran (↓) NR Iran (↓) Iran (↑) NR Iran (↑) Ukraine (↓) Vietnam (↑) Ukraine (↓) Ukraine (↓) Ukraine (↑) Vietnam (↓) Vietnam (↓) Vietnam (↓) Njeru et al (2016) [ 23 ] NS NR NR Norredam et al (2014) [ 20 ] NR NR NR NR NR van Oostrum et al (2011) [ 24 ] NR NR NR NR NR Yun et al (2012) [ 21 ] NS NR …”
Section: Resultsmentioning
confidence: 99%
“…Of the seven studies included, four examined D.M. prevalence in refugees [ 20 , [24] , [25] , [26] ]. When compared with native populations, refugees demonstrated significantly higher rates of D.M.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Iranian population had the highest burden of psychiatric diseases (depression n = 2, insomnia n = 2, anxiety n = 1), followed by EBP, dental concerns, and GERD (n = 2 for each). In a study done in California on Iranian refugees, they seemed to have a higher burden of diabetes mellitus and tobacco use than the general California population [34]. While the results may not be congruent, psychiatric diseases and tobacco use have been linked [35, 36].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some studies reported a high prevalence of tobacco smoking among refugees. For example, a higher prevalence of tobacco smoking (16.7%) compared to the general public (14.4%) was found among refugees from Iran, Ukraine, and Vietnam in California [ 15 ]. Approximately half of Somali refugees in Minnesota reported tobacco use [ 16 ].…”
Section: Introductionmentioning
confidence: 99%